Studi Pengaruh Rasio Masukan Sumber V/III Terhadap Distribusi Sb dan Karakteristik Kelistrikan Lapisan Tipis GaAs1-x Sbx yang Ditumbuhkan dengan Teknik MOCVD [On the Study of the Effect of Source Input V/III to the Distribution of Sb and Electricity.....] - Andi Suhandi; Pepen Arifin; Maman Budiman; Muhamad Barmawi (Institut Teknologi Bandung, 2007)
The study of the dependence of the Sb distribution in GaAs1-xSbx films and the electric properties of the GaAs1-xSbx filmsgrown by MOCVD technique using TMGa, TDMAAs, and TDMASb to the V/III source input ratio has been done. The Sbsolid composition in GaAs1-xSbx film was determined by using Vegards law from the shift of the peak intensity of X-raydiffraction pattern. Electric properties of the GaAs1-xSbx films were investigated through room temperature Hall effectmeasurement. The results suggest that the concentration of Sb incorporation into the GaAs1-xSbx films is stronglyaffected by V/III source input ratio. For V/III source input ratio of unity, the Sb distribution coefficient, which is theratio of the Sb composition in GaAs1-xSbx solid to the Sb vapor input mole fraction, is nearly unity. The Sb distributioncoefficient decreases with increasing of V/III source input ratio, for V/III input ratio langer than 1. The range of carriermobility are between 200 â 430 cm2/V.s, depending on the V/III input ratio, and the Sb composition. The highest carriermobility occurred at V/III input ratio of approximately one.